2018
DOI: 10.1103/physreva.98.050101
|View full text |Cite
|
Sign up to set email alerts
|

Bridging thermodynamics and metrology in nonequilibrium quantum thermometry

Abstract: Single-qubit thermometry presents the simplest tool to measure the temperature of thermal baths with reduced invasivity. At thermal equilibrium, the temperature uncertainty is linked to the heat capacity of the qubit, however the best precision is achieved outside equilibrium condition. Here, we discuss a way to generalize this relation in a non-equilibrium regime, taking into account purely quantum effects such as coherence. We support our findings with an experimental photonic simulation.Introduction:-Identi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
51
2
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(57 citation statements)
references
References 49 publications
2
51
2
2
Order By: Relevance
“…On the other hand, thermal fluctuations often spoil the effectiveness of quantum metrological protocols, the most dramatic case being represented by quantum interferometry, where an infinitesimal amount of noise is enough to kill Heisenberg scaling and reinstates the shot noise limit [ 19 ]. In turn, the effect of temperature has been analyzed in different metrological contexts, for example the out-of-equilibrium regimes [ 20 ] and phase estimation in Gaussian states [ 21 ]. For these reasons, we extend here the analysis to the more realistic case of complex systems at thermal equilibrium and discuss in detail the interplay among thermal fluctuations and time evolution in making the qubit an effective probe for the cutoff frequency of its environment.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, thermal fluctuations often spoil the effectiveness of quantum metrological protocols, the most dramatic case being represented by quantum interferometry, where an infinitesimal amount of noise is enough to kill Heisenberg scaling and reinstates the shot noise limit [ 19 ]. In turn, the effect of temperature has been analyzed in different metrological contexts, for example the out-of-equilibrium regimes [ 20 ] and phase estimation in Gaussian states [ 21 ]. For these reasons, we extend here the analysis to the more realistic case of complex systems at thermal equilibrium and discuss in detail the interplay among thermal fluctuations and time evolution in making the qubit an effective probe for the cutoff frequency of its environment.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, it has been recently shown that optimal estimation by quantum probes may be achieved also at finite time, i.e. when the probe has not reached stationarity, and it is still in an outof-equlibrium state [18][19][20][21][22][23][24]. Following this results, we address here open quantum systems out-of-equilibrium as possible quantum probes for the characterisation of their environment.…”
Section: Introductionmentioning
confidence: 80%
“…The superscripts in Eqs. (11) and (12) denote the order in ̇ of the calculated quantity. Specifically, the WBL expressions for -dependent contributions to the particle number, energy, and entropy are given by (See Ref.…”
Section: The Quasi-static Limitmentioning
confidence: 99%
“…Next, consider shifting the dot's energy at a finite rate. Some preliminary notes are in place: (i) As mentioned above, recent analytical studies [4][5][6][7][10][11][12][13][14][15] have evaluated the lowest order (in the driving rate) corrections to thermodynamic functions and fluxes. To approach this limit in the numerical simulations we need to use relatively slow shift rates, for which deviations from the quasistatic limit are small, implying relatively large numerical errors.…”
Section: Finite Dot-level Driving Ratementioning
confidence: 99%
See 1 more Smart Citation